(untitled) (Intent Research Scientific Journal, 2025)
The textile industry is one of the important sectors in the economy of Uzbekistan, playing an important role in the sustainable growth of the country’s export potential. In recent years, state programs and strategies to support the entry of small businesses into international markets have been consistently implemented. This article analyzes the mechanisms for small businesses to enter global competition in the textile sector of Uzbekistan, the dynamics of export indicators, and existing problems. During the study, based on statistical data, the factors of economic growth, the impact of innovative management on export activities are highlighted, and scientific recommendations are given on effective strategic directions.